Hubungan Ekspresi CD133 dan EGFR Terhadap Derajat Keganasan pada Karsinoma Ovarium - Agung Dwi Suprayitno; Dyah Fauziah; Gondo Mastutik (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2021)
BackgroundOvarian carcinoma account for 90% of all malignant ovarian tumors. Epidermal Growth Factor Receptor (EGFR), also known asErbB1/HER1, has an important role in tumor cell proliferation. CD133 is a marker for hematopoietic stem cell and it is involved in tumorcell proliferation, self renewal and cell differentiation. The objective to analyze the expression of CD 133 and EGFR in high grade andlow grade ovarian carcinoma, and to determine the correlation between the expression of CD133 and EGFR expression in ovariancarcinoma.MethodsThe study was conducted with observational and cross sectional method on paraffin blocks of patients diagnosed as ovariancarcinoma from 1 January until 31 December 2017 in Dr. Soetomo Hospital. Ovarian carcinoma was divided into 2 grade, low gradeand high grade. Immunohistochemistry for EGFR and CD133 was performed. Immuno-reactive Score (IRS) was applied to evaluatethe expression of EGFR and CD133. The difference expression of CD133 and EGFR in low grade and high grade ovarian carcinomawas analyzed with Mann-Whitney test. Correlation between CD133 with EGFR was analyzed with Spearman test.ResultsThere were significant difference in expression of CD133 (p=0.0001) and EGFR (p=0.0005) in high grade and low grade OvarianCarcinoma. There was significant positive correlation between CD133 and EGFR expression in Ovarian Carcinoma (p=0.035; r=0.37)ConclusionExpression of CD133 and EGFR were higher in high grade ovarian carcinoma. The higher expression of CD133 will increaseexpression of EGFR in ovarian carcinoma. Both markers may be used as prognostic factor.